Lipocalin 2: An Emerging Player in Iron Homeostasis and Inflammation - Xiao, Xia; Yeoh, Beng San; Vijay-Kumar, Matam (Annual review of nutrition, 2017)
Lipocalin 2 (Lcn2), an innate immune protein, has emerged as a critical iron regulatory protein during physiological and inflammatory conditions. As a bacteriostatic factor, Lcn2 obstructs the siderophore iron-acquiring strategy of bacteria and thus inhibits bacterial growth. As part of host nutritional immunity, Lcn2 facilitates systemic, cellular, and mucosal hypoferremia during inflammation, in addition to stabilizing the siderophore-bound labile iron pool. In this review, we summarize recent advances in understanding the interaction between Lcn2 and iron, and its effects in various inflammatory diseases. Lcn2 exerts mostly a protective role in infectious and inflammatory bowel diseases, whereas both beneficial and detrimental functions have been documented in neurodegenerative diseases, metabolic syndrome, renal disorders, skin disorders, and cancer. Further animal and clinical studies are necessary to unveil the multifaceted roles of Lcn2 in iron dysregulation during inflammation and to explore its therapeutic potential for treating inflammatory diseases.